2014
DOI: 10.1007/s13181-014-0430-3
|View full text |Cite
|
Sign up to set email alerts
|

Is It Prime Time for Alpha2-Adrenocepter Agonists in the Treatment of Withdrawal Syndromes?

Abstract: The need to treat withdrawal syndromes is a common occurrence in outpatient, inpatient ward, and intensive care unit (ICU) settings. A PubMed and Google Scholar search using alpha2-adrenoreceptor agonist (A2AA), specific A2AA agents, withdrawal syndrome and nicotine, and alcohol and opioid withdrawal terms was performed. A2AA agents appear to be able to modulate many of the signs and symptoms of significant withdrawal syndromes but are also capable of significant side effects, which can limit clinical use. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 136 publications
1
25
1
Order By: Relevance
“…Two other α2-adrenergic receptor agonists have shown promise in reducing opioid withdrawal–clonidine and lofexidine (32). Walsh et al evaluated the modulation effects on opioid withdrawal of clonidine and lofexidine, finding that both drugs reduced the objective sympathomimetic response to naloxone-precipitated withdrawal but with little effect on subjective measures of opioid withdrawal (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other α2-adrenergic receptor agonists have shown promise in reducing opioid withdrawal–clonidine and lofexidine (32). Walsh et al evaluated the modulation effects on opioid withdrawal of clonidine and lofexidine, finding that both drugs reduced the objective sympathomimetic response to naloxone-precipitated withdrawal but with little effect on subjective measures of opioid withdrawal (33).…”
Section: Discussionmentioning
confidence: 99%
“…Walsh et al evaluated the modulation effects on opioid withdrawal of clonidine and lofexidine, finding that both drugs reduced the objective sympathomimetic response to naloxone-precipitated withdrawal but with little effect on subjective measures of opioid withdrawal (33). The prior findings are compounded in a 2014 review of several clinical trials by Albertson et al, where in addition, lofexidine was found to be more effective in reducing the symptoms of opioid withdrawal than placebo and reduced the number of days required for detoxification when compared to methadone (32). …”
Section: Discussionmentioning
confidence: 99%
“…Based on our current results, it would seem that conducting clinical trials with lorcaserin in heroin addicts will be a promising venture. Clonidine is a prescription drug for opioid addicts [14]. Pre-clinical studies indicate that clonidine suppresses behavioral sensitization and withdrawal in heroin-treated subjects by acting on α2-adrenoceptor, a Gαi protein-coupled receptor that has an inhibitory effect on noradrenergic neurons in the central nervous system [16].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies indicate that clonidine suppresses behavioral sensitization and withdrawal in heroin-treated subjects by acting on α2-adrenoceptor, a Gαi protein-coupled receptor that has an inhibitory effect on noradrenergic neurons in the central nervous system [16]. However, clonidine induces a number of adverse effects, including bradycardia, hypotension, sedation and withdrawal syndrome [14], which limit its application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation